The Economic Aspects of Advertising - Kaldor, Nicholas (Review of Economic Studies, 1950)
The Economic Aspects of Advertising Get access Nicholas Kaldor Nicholas Kaldor Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 18, Issue 1, 1950, Pages 1–27, https://doi.org/10.2307/2296103 Published: 01 January 1950